(untitled) (Филолошке студије, 2020)
The author analyzes the literary heritage of the Russian postmodernist writer Vladimir Sharov in the context of travel images. The article considers novels “Be like children” and “Return to Egypt”. The author believes that the writer actualized in his texts the problems of movement as of a social and cultural journey, like trauma, nostalgia and forgetting. The real and imaginary travels of characters in the prose by V.Sharov can be described in the categories of absurdity and meaninglessness. Travel images do not actualize spatial migrations, but they visualize contradictions and paradoxes of the development of Russian identity as a deformed one. The author analyzes travels in V. Sharov’s prose as invented cultural traditions. The travel discourse in the texts by V. Sharov became the result of the development of modern Russia that emerged as modern before modern and modern without modern. The author of the article assumes that the travel in V. Sharov’s prose gradually loses its connection with reality, transforming into travel as a construct and travel as memory. The forced travels of his prose characters became imaginary pilgrimages and attempts of the Russian people, regarded as a hostage of Russian history, to escape. The writer imagined Russian history as a cyclical social and cultural journey. The motifs of travel in V. Sharov’s prose are presented in a variety of forms, including a novel in letters, a traditional postmodern novel, and an imitation of hagiographic texts.